Economic and Social Policies During Covid-19 Period: Relief Plan of Uzbekistan - Konstantin Ivanovich Kurpayanidi, Alisher Makhmudovich Abdullaev, Nilufar Muratovna Nabieva , Elnorakhon Abdukarimovna Muminova, Guzal Sherovna Honkeldieva (International Journal of Advanced Science and Technology, 2020)
The coronavirus epidemic of COVID-19 has devastated the Chinese economy and is expanding worldwide. The nature of the infection and its economic effects remain extremely unpredictable, making it difficult for policymakers to devise an effective macro-economic policy solution. In order to alleviate the negative economic impact, this paper explores the set of measures that are proposed and policies which will help households, businesses, and the government to combat the consequences of COVID-19. The current study begins by analyzing viewpoints of world experts, particularly economic specialists in the United States who suggested a set of activities that would benefit the whole economy during uncertain times. The paper also examines the anti-crisis plan to support the economic situation in Uzbekistan due to coronavirus and global crisis. These scenarios demonstrate the scale of costs that might be avoided by greater investment in social support programs in the world economy but particularly in the Uzbekistan case.